Portable Differential Detection of CTX-M ESBL Gene Variants, blaCTX-M-1 and blaCTX-M-15, from Escherichia coli Isolates and Animal Fecal Samples Using Loop-Primer Endonuclease Cleavage Loop-Mediated Isothermal Amplification - Owen Higgins; Alexandra Chueiri; Louise O'Connor; Sinéad Lahiff; Liam Burke; Dearbhaile Morris; Nicola Maria Pfeifer; Belén González Santamarina; Christian Berens; Christian Menge; Manuela Caniça; Vera Manageiro; et al. (Microbiology Spectrum, 2023)
ABSTRACT Cefotaximase-Munich (CTX-M) extended-spectrum beta-lactamase (ESBL) enzymes produced by Enterobacteriaceae confer resistance to clinically relevant third-generation cephalosporins. CTX-M group 1 variants, CTX-M-1 and CTX-M-15, are the leading ESBL-producing Enterobacteriaceae associated with animal and human infection, respectively, and are an increasing antimicrobial resistance (AMR) global health concern. The blaCTX-M-1 and blaCTX-M-15 genes encoding these variants have an approximate nucleotide sequence similarity of 98.7%, making effective differential diagnostic monitoring difficult. Loop-primer endonuclease cleavage loop-mediated isothermal amplification (LEC-LAMP) enables rapid real-time multiplex pathogen detection with single-base specificity and portable on-site testing. We have developed an internally controlled multiplex CTX-M-1/15 LEC-LAMP assay for the differential detection of blaCTX-M-1 and blaCTX-M-15. Assay analytical specificity was established using a panel of human, animal, and environmental Escherichia coli isolates positive for blaCTX-M-1 (n = 18), blaCTX-M-15 (n = 35), and other closely related blaCTX-Ms (n = 38) from Ireland, Germany, and Portugal, with analytical sensitivity determined using probit regression analysis. Animal fecal sample testing using the CTX-M-1/15 LEC-LAMP assay in combination with a rapid DNA extraction protocol was carried out on porcine fecal samples previously confirmed to be PCR-positive for E. coli blaCTX-M. Portable instrumentation was used to further analyze each fecal sample and demonstrate the on-site testing capabilities of the LEC-LAMP assay with the rapid DNA extraction protocol. The CTX-M-1/15 LEC-LAMP assay demonstrated complete analytical specificity for the differential detection of both variants with sensitive low-level detection of 8.5 and 9.8 copies per reaction for blaCTX-M-1 and blaCTX-M-15, respectively, and E. coli blaCTX-M-1 was identified in all blaCTX-M positive porcine fecal samples tested. IMPORTANCE CTX-M ESBL-producing E. coli is an increasing AMR public health issue with the transmission between animals and humans via zoonotic pathogens now a major area of interest. Accurate and timely identification of ESBL-expressing E. coli CTX-M variants is essential for disease monitoring, targeted antibiotic treatment and infection control. This study details the first report of portable diagnostics technology for the rapid differential detection of CTX-M AMR markers blaCTX-M-1 and blaCTX-M-15, facilitating improved identification and surveillance of these closely related variants. Further application of this portable internally controlled multiplex CTX-M-1/15 LEC-LAMP assay will provide new information on the transmission and prevalence of these CTX-M ESBL alleles. Furthermore, this transferable diagnostic technology can be applied to other new and emerging relevant AMR markers of interest providing more efficient and specific portable pathogen detection for improved epidemiological surveillance.